Analisis Putusan Nomor 46 PK/Ag/2020 juncto Putusan Nomor 847/Pdt.G/2019/PA.Tng) Terhadap Sengketa Hybrid Contract - Zahro, Ana Latifatuz; Fauzi, Moh. Yasir; Pratiwi, Nindia (Universitas Islam Negeri Raden Intan Lampung, 2024)
Tangerang Religious Court Decision Number 847/Pdt.G/2019/PA.Tng which has legal force is still requested for judicial review. So that the Supreme Court of the Republic of Indonesia in Decision Number 46 PK/Ag/2020 canceled decision Number 847/Pdt.G/2019/PA.Tng and re-adjudicated with the ruling of refusal. There are differences of opinion in legal considerations between Judex Facti Decision Number 847/Pdt.G/2019/PA.Tng and Judex Juris Decision Number 46 PK/Ag/2020. The qualitative research method uses a type of library research with descriptive analytical research. The results of the discussion show that Judex Facti granted the tort claim with his legal consideration that the elements of tort were proven. While Judex Juris the elements of tort are not proven. Legal interpretation as the core of legal hermeneutics aims as an intermediary in the context of legal discovery by judges in court. The method of legal hermeneutics with interpretation, namely conducting an examination of the texts of sharia economic dispute documents. In order to avoid differences of opinion in terms of sharia economic disputes, especially tort or default, it is necessary to make a circular letter of the supreme court. In sharia transactions, the parties before signing the contract should be read and researched to understand the contents of the contract.Keywords: Hermeneutics; Sharia Economic Dispute; Hybrid Contract